The Role of Parenting Patterns of Parents and Teachers in Developing Emotional Intelligence in Early Childhood - Lelen Novita; Susi Herawati; Rizki Pebrina; Silvia Susrizal; Adam Mudinillah (Yayasan Adra Karima Hubbi, 2024)
Parenting patterns of parents and teachers in responding to the rampant problems that occur regarding the emotions of early childhood children are very important to note. Where the need for a primary role for parents in educating. With the existence of good parenting patterns in the family, it will produce personality, and have a wise attitude so that it has a great influence when growing up. The impact is that children's emotions will be easy to control because they have been educated and taught in their daily environment.Research purposesThis is to determine the role of parents and teachers in developing emotional intelligence in early childhood.This research methodUsing quantitative methods, based on data obtained through the distribution of questionnaires using the online Google Form platform, researchers found a phenomenon of parents and teachers who are concerned about emotional intelligence.Research resultexplains that the role of parents and teachers in developing emotional intelligence in early childhood has a big influence, the existence of motivators and educators obtained from parents, and supervision applied to teachers at school.Research conclusionexplains the important role of parents and teachers in dealing with the emotions of early childhood.Limitations in researchThis is a researcher who only conducted research on the role of parenting patterns and teachers in developing early childhood emotional intelligence.Researchers hopeto further research so that the same research can be carried out but with a wider scope so that this research can be continued.This researcher also recommendsto further researchers to use this research as a benchmark to achieve the same goal, so that readers can also understand the purpose of research on parenting patterns of parents and teachers in developing emotional intelligence in early childhood.